Mobile veterinary clinics in the drylands of Kenya: Securing pastoralists’ livelihoods by bringing services close - Omondi, Immaculate A.; Baltenweck, Isabelle; Kinuthia, Emmanuel; Kirui, Leonard; Njoroge-Wamwere, George; Bett, Bernard K.; Munene, Ambrose; Onle, S.; Dida, D.; Kiara, Henry K. (Informa UK Limited, 2021)
Livestock productivity for pastoralist households, who depend upon their livestock as a source of livelihood, is constrained by infectious diseases among other factors. Pastoralists in the arid and semi-arid lands (ASALs) of the Horn of Africa lack access to livestock health inputs and services. To assess the profitability of private animal health service delivery, mobile veterinary clinics were piloted in three ASAL counties in Kenya. Our findings reveal the positive impact of the clinics on animal health provision as well as policy and regulatory factors that affect its viability.